Enlightenment : a novel - Perry, Sarah, 1979- (Mariner Books, 2024)
"Thomas Hart and Grace Macaulay have lived all their lives in the small Essex town of Aldleigh. Though separated in age by three decades, the pair are kindred spirits--torn between their commitment to religion and their desire to explore the world beyond their small Baptist community. It is two romantic relationships that will rend their friendship, and in the wake of this rupture, Thomas develops an obsession with a vanished nineteenth-century astronomer said to haunt a nearby manor, and Grace flees Aldleigh entirely for London. Over the course of twenty years, by coincidence and design, Thomas and Grace will find their lives brought back into orbit as the mystery of the vanished astronomer unfolds into a devastating tale of love and scientific pursuit. Thomas and Grace will ask themselves what it means to love and be loved, what is fixed and what is mutable, how much of our fate is predestined and written in the stars, and whether they can find their way back to each other"--